Performing pooja of the fishing boats - Mumbai Archive Project Team (Jio Institute, 2024)
Fishing boats are cleaned, painted, and decorated with flowers, bright flags, and coconut leaves. A puja (prayer ritual) is performed on the boats to invoke divine blessings for a safe and prosperous fishing season.